Nonlinear Behavior of Reinforced Concrete Frames Equipped with and without Steel Plate Shear Wall under Sequence of Real and Artificial Earthquakes - Hamze Rouhi; Majid Gholhaki (Advances in Civil Engineering)
There is a possibility of increasing structural damage in the sequential earthquake compared to the main earthquake according to past earthquakes. This study investigates the effects of seismic sequence on the behavior and increased response of reinforced concrete frames (RCF) with/without steel plate shear walls (SPSW). Four systems of 4, 8, 12, and 24 story, which represent low-, mid-, and high-rise structures, are designed and subjected to nonlinear time history analysis under critical single and consecutive records with real, repetitive, and randomized methods. The seismic scenarios used include sequential recorded critical earthquakes. The analysis showed that the predominant period of the after-shock significantly influences the post main-shock response. In RCF with and without SPSW, real seismic sequence increases the ratio of peak maximum interstory drift by an average of 2, 2 times the similar demand in the main shock, and increases the ratio of maximum ductility demand by 1.52 and 1.65 times in the structure, respectively. In an artificial sequence, the ratio of peak maximum interstory drift demand increase is in 100%, 150%, and 200% after-shocks, In the iteration method, it is equal to 1.2, 2.0, and 2.6 times the main shock in RCF with SPSW and 1.9, 3.2, and 4.8 times the main shock in RCF without SPSW. After-shocks may change the direction and magnitude of residual displacement in real and artificial seismic sequences. Continuation of the equation to calculate the demand for seismic sequence ductility was extracted.